Experimental Basis and New Insights for Cell Therapy in Chronic Obstructive Pulmonary Disease - de Faria, Carolina Arruda; Kozma, Rodrigo de las Heras; Stessuk, Talita; Ribeiro-Paes, Joao Tadeu [UNESP] (Humana Press Inc, 2012)
Chronic Obstructive Pulmonary Disease (COPD) can be briefly described as air flow limitation and chronic dyspnea associated to an inflammatory response of the respiratory tract to noxious particles and gases. Its main feature is the obstruction of airflow and consequent chronic dyspnea. Despite recent advances, and the development of new therapeutic, medical and clinical approaches, a curative therapy is yet to be achieved. Therapies involving the use of tissue-specific or donor derived cells present a promising alternative in the treatment of degenerative diseases and injuries. Recent studies demonstrate that mesenchymal stem cells have the capacity to modulate immune responses in acute lung injury and pulmonary fibrosis in animal models, as well as in human patients. Due to these aspects, different groups raised the possibility that the stem cells from different sources, such as those found in bone marrow or adipose tissue, could act preventing the emphysematous lesion progression. In this paper, it is proposed a review of the current state of the art and future perspectives on the use of cell therapy in obstructive lung diseases.
Keywords: Chronic obstructive pulmonary disease; Cell therapy; Stem cells; Bone marrow